Analysis of Economic Growth in Central Java 2003 – 2019 - Muhammad Fauzi Huda; Sitti Retno Faridatussalam (International Journal of Economics and Management Research, 2025)
Developing countries generally face economic challenges like high inflation and slow growth. Inflation has dual positive and negative impacts; high inflation can hinder economic growth and vice versa. Additionally, inflation affects unemployment; rising inflation tends to decrease real income and increase poverty. This study evaluates economic growth in Central Java Province from 2003-2019 using a quantitative time series approach with secondary data and OLS for multiple linear regression. T-test results indicate that inflation, poverty, and unemployment did not significantly impact economic growth in Central Java during this period.